Sosialisasi Dan Pelatihan Penggunaan Aplikasi Buku Warung Bagi Para UMKM Di Kelurahan Binong - Ulfah Ulfah; Yohana Yohana; Helena Fransiska Watratan; Meutya Maharani; Muhammad Rifan; Nurul Wulansari; Ratri Nur Indah Sari (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
In the current digital era, Micro, Small and Medium Enterprises (MSMEs) need digital tools to facilitate their business processes. Binong Subdistrict, as one of the subdistricts that has many MSMEs, faces challenges in encouraging technology adoption among MSME owners. To overcome this problem, the authors introduce BukuWarung, a digital financial platform, as a practical solution to optimize financial recording. The process involves training and mentoring structured in four steps: outreach, training and mentoring, and evaluation. The results show that MSMEs now better understand the important role of financial management and have successfully adopted BukuWarung for their financial recording needs. In conclusion, socialization and training on the use of the Buku Warung application in Binong Village succeeded in increasing the understanding and skills of MSMEs in utilizing digital technology to support their business.